Cohort profile: the Western Cape Pregnancy Exposure Registry (WCPER) - Landon Myer; Amy L Slogrove; Ushma Mehta; Mary-Ann Davies; Max Kroon; Greg Petro; Alexa Heekes; Andrew Boulle; Karen Fieggen; Chantal Stewart; Ayesha Osman; Natasha Rhoda; et al. (BMJ Open)
Purpose The Western Cape Pregnancy Exposure Registry (PER) was established at two public sector healthcare sentinel sites in the Western Cape province, South Africa, to provide ongoing surveillance of drug exposures in pregnancy and associations with pregnancy outcomes.Participants Established in 2016, all women attending their first antenatal visit at primary care obstetric facilities were enrolled and followed to pregnancy outcome regardless of the site (ie, primary, secondary, tertiary facility). Routine operational obstetric and medical data are digitised from the clinical stationery at the healthcare facilities. Data collection has been integrated into existing services and information platforms and supports routine operations. The PER is situated within the Provincial Health Data Centre, an information exchange that harmonises and consolidates all health-related electronic data in the province. Data are contributed via linkage across a unique identifier. This relationship limits the missing data in the PER, allows validation and avoids misclassification in the population-level data set.Findings to date Approximately 5000 and 3500 pregnant women enter the data set annually at the urban and rural sites, respectively. As of August 2021, >30 000 pregnancies have been recorded and outcomes have been determined for 93%. Analysis of key obstetric and neonatal health indicators derived from the PER are consistent with the aggregate data in the District Health Information System.Future plans This represents significant infrastructure, able to address clinical and epidemiological concerns in a low/middle-income setting.